2010
DOI: 10.1063/1.3437645
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nb-donor and Fe-acceptor dopants in (Bi1/2Na1/2)TiO3–BaTiO3–(K0.5Na0.5)NbO3 lead-free piezoceramics

Abstract: Articles you may be interested inLead-free piezoelectric ceramics based on (0.97−x)K0.48Na0.52NbO3-0.03Bi0.5(Na0.7K0.2Li0.1)0.5ZrO3-xB0.5Na0.5TiO3 ternary system J. Appl. Phys. 114, 124107 (2013) Effect of Nb-donor and Fe-acceptor dopants in "Bi 1/2 Na 1/2 …TiO 3 -BaTiO 3 -"K 0.5 Na 0.5 …NbO 3 lead-free piezoceramics The role of Fe as an acceptor and Nb as a donor in ͓0.94− x͔͑Bi 1/2 Na 1/2 ͒TiO 3 -0.06BaTiO 3 −x ͑K 0.5 Na 0.5 ͒NbO 3 ͑100xKNN͒ ͑x = 0.02 and 0.03͒ lead-free piezoceramics was investigated. X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 48 publications
(55 reference statements)
2
41
0
Order By: Relevance
“…43 The presence of such defect dipoles can stabilize ferroelectric order in the material and therefore increase the T d . 44 The subsequent decrease in T d due to higher temperature. 46 The decrease in both the room temperature d 33 and the T d which is observed at higher levels of Fe substitution may be associated with limited substitution of Fe in this material.…”
Section: Discussionmentioning
confidence: 99%
“…43 The presence of such defect dipoles can stabilize ferroelectric order in the material and therefore increase the T d . 44 The subsequent decrease in T d due to higher temperature. 46 The decrease in both the room temperature d 33 and the T d which is observed at higher levels of Fe substitution may be associated with limited substitution of Fe in this material.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Here, we use the term, giant strains, to distinguish them from the conventional electric-field-induced strain in poled ferroelectric (FE) materials in that the onset of these strains requires a certain threshold electric field level (referred to as E pol hereafter), but this electric-field-induced poling state becomes unstable with little trace of perceivable piezoelectricity when the field is removed. 13,14 This phenomenological feature categorized the materials with such strain behavior as a new material class designated as incipient piezoceramics. 15 In spite of the exceptionally large strains available in the incipient piezoceramics, there are at least three challenges to be overcome for versatile applications.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Later, it was shown that this near non-polar P4bm phase is favored when Na þ ions are replaced by bigger isovalent ions such as K þ (Ref. 32) or when A-site vacancy is created, [33][34][35][36][37] while unfavored with acceptor dopants generating oxygen vacancies. 33,37 In the meantime, Ma et al 23 proposed another "relaxor antiferroelectric" model with the terminology being the same with the model of Dorcet et al 17 but with the underlying physics being completely different.…”
mentioning
confidence: 99%